(3eLehYI aj GdgfOSIs - (3GdgGeGfjs ((3CHh YHO Gddg s)
(3ChdgG (B:s
(3bGd gPG GdJi Yed YdjgG GbdjOS ai GdebGOjQ GdJi fSHJgG Cf GdYde fSHI GdebGOjQ hJfGSHgG Ydi GdCMcGe s
(3BNQgG (B:s
(3hPdc eG CQOfGg JeJ cJGHI GdQSGdI HYhf Gddg JYGdi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdQGHYs
(3HgG fXGe GdJYbjHIs
(3Jdjg QSGdI ai HjGf eUGOb EbdjOS dQLd eLghds
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdQjGVjGJs